Answer:
sin θ =
![(√(6) )/(3)](https://img.qammunity.org/2021/formulas/mathematics/high-school/lnlhzxyocxfuvafv4tcd7ldd15xkic2td2.png)
Explanation:
Given that,
cos θ =
![(√(3) )/(3)](https://img.qammunity.org/2021/formulas/mathematics/high-school/9fk3ek6ugopkephalyrcrf79zd0fery7do.png)
From the trigonometric functions,
cos θ =
![(adjacent)/(hypotenus)](https://img.qammunity.org/2021/formulas/mathematics/high-school/fgelijp7i614tx5kn1pr2c5uuu4knp94zi.png)
⇒ adjacent =
, and the hypotenuse = 3
Let the opposite side be represented by x, applying the Pythagoras theorem we have;
=
+
![/opp/^(2)](https://img.qammunity.org/2021/formulas/mathematics/college/kpttaarc7kzoiv9bqkbcm0igqml3fwt2qc.png)
=
+
![x^(2)](https://img.qammunity.org/2021/formulas/mathematics/middle-school/8h1y97mwj8mwic83188qjkhvavc5d1kao6.png)
9 = 3 +
![x^(2)](https://img.qammunity.org/2021/formulas/mathematics/middle-school/8h1y97mwj8mwic83188qjkhvavc5d1kao6.png)
= 9 - 3
= 6
x =
![√(6)](https://img.qammunity.org/2021/formulas/mathematics/middle-school/wc7gsvgmyxbwiapo5r1akzeqm3xwa3augt.png)
Thus, opposite side =
![√(6)](https://img.qammunity.org/2021/formulas/mathematics/middle-school/wc7gsvgmyxbwiapo5r1akzeqm3xwa3augt.png)
So that,
sin θ =
![(opposite)/(hypotenuse)](https://img.qammunity.org/2021/formulas/mathematics/middle-school/rt7pn6xj737o5vkvyd45c3tvp6uv2axdbt.png)
=
![(√(6) )/(3)](https://img.qammunity.org/2021/formulas/mathematics/high-school/lnlhzxyocxfuvafv4tcd7ldd15xkic2td2.png)
Therefore,
sin θ =
![(√(6) )/(3)](https://img.qammunity.org/2021/formulas/mathematics/high-school/lnlhzxyocxfuvafv4tcd7ldd15xkic2td2.png)